Proceedings of the Genetic and Evolutionary Computation Conference Companion 2022
DOI: 10.1145/3520304.3534069
|View full text |Cite
|
Sign up to set email alerts
|

Choosing the right algorithm with hints from complexity theory

Abstract: Choosing a suitable algorithm from the myriads of different search heuristics is difficult when faced with a novel optimization problem. In this work, we argue that the purely academic question of what could be the best possible algorithm in a certain broad class of black-box optimizers can give fruitful indications in which direction to search for good established optimization heuristics. We demonstrate this approach on the recently proposed DLB benchmark, for which the only known results are O(n 3 ) runtimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other algorithms were conducted with 50 independent runs and terminated when the full Pareto front was covered. We set α = 3 as in the paper (Wang, Zheng, and Doerr 2024) standard bit-wise mutation for NSGA-II, and set µ = n − 1 (at least n − 1 as suggested in Theorem 18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other algorithms were conducted with 50 independent runs and terminated when the full Pareto front was covered. We set α = 3 as in the paper (Wang, Zheng, and Doerr 2024) standard bit-wise mutation for NSGA-II, and set µ = n − 1 (at least n − 1 as suggested in Theorem 18).…”
Section: Methodsmentioning
confidence: 99%
“…Oliveto et al (2018) proved that the Metropolis algorithm solves their VALLEY function (which is different from the VALLEY problem defined in (Droste, Jansen, and Wegener 2000)) more efficiently than simple evolutionary algorithms (EAs). Wang, Zheng, and Doerr (2024) showed that the Metropolis algorithm solves the DECEPTIVELEADINGBLOCKS (DLB) function in expected time of O(n 2 ), while all (1+1)-elitist unary unbiased black-box algorithms have an expected runtime of Ω(n 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation